1995
DOI: 10.1136/vr.136.20.511
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various levels of T-2 toxin in the immune system of growing pigs

Abstract: Four groups of seven-week-old pigs weighing about 9 kg were fed for three weeks a prestarter that contained 0.5, 1.0, 2.0 or 3.0 mg/kg of highly purified T-2 toxin. The average daily intakes of toxin by the pigs were 0.38, 0.81, 1.24 and 1.43 mg, respectively. The experimental and control pigs were immunised with 5 ml aluminum hydroxide gel-absorbed purified horse globulin on the first and fourth days of the treatment period. Blood samples were withdrawn on days 7, 14 and 21 and used for the determination of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
3
1

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 0 publications
3
46
3
1
Order By: Relevance
“…including lymphocyte proliferation responses, monocyte maturation, and host defense against pathogens (60)(61)(62)(63). Another recent study (62) demonstrated that ribosomal inactivation decreases the production of antibacterial mediators such as reactive oxygen species by attenuating the expression of TLRs [TLR4, TLR2, and TLR6 (62)].…”
Section: Discussionmentioning
confidence: 99%
“…including lymphocyte proliferation responses, monocyte maturation, and host defense against pathogens (60)(61)(62)(63). Another recent study (62) demonstrated that ribosomal inactivation decreases the production of antibacterial mediators such as reactive oxygen species by attenuating the expression of TLRs [TLR4, TLR2, and TLR6 (62)].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the study was to evaluate the effect of a 200 μg dose of synthetic T-2 toxin kg -1 feed (approximately 20 μg T-2 kg -1 BW) administered orally to gilts over a period of 42 days. The applied dose was smaller than that used by Rafai et al (1995) in whose experiment, piglets were administered feed containing a 29 μg dose of T-2 kg -1 BW for 21 days. The percentages of lymphocyte subpopulations and interleukin mRNA expression levels were analyzed in samples of ileal Peyer's patches containing unfractionated cells.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure to the T-2 toxin causes leukopenia and cell depletion in lymphoid organs, it inhibits erythropoiesis in the bone marrow and spleen (Nagata et al 2001, Grizzle et al 2004, Parent-Massin 2004. T-2 intoxication can significantly impair antibody production (Niyo et al 1988, Kamalavenkatesh et al 2005, Li et al 2006a, it reduces the proliferative response of lymphocytes (Rafai et al 1995, Kamalavenkatesh et al 2005 and hinders the development of dendritic cells (Hymery et al 2006, Hymery et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Although the T-2 toxin level has not been regulated in EU and Turkey, these concentrations were lower than the toxic levels of T-2 toxin that have been reported as 100 μg/kg for animals by Mabbett 1 and 500μg/kg for growing pigs by Rafai et al 23 . One of maize gluten feed samples contained 102.35 μg/kg of T-2 toxin, which is higher than 100 μg/kg.…”
mentioning
confidence: 94%